The Influence of Capital Structure, Sales Growth on Financial Performance, with Liquidity and Environment, Social and Government Rating as Control Variables and Moderated by Company Size - Jessika Santoso Yohana; Ignatius Roni Setyawan (Green Publisher Indonesia, 2024)
This study aims to examine the influence of Capital Structure and Sales Growth on Financial Performance with Liquidity and Environment, Social and Governance Rating as Control Variables and moderated by the Size of the Company. This study also uses data from manufacturing companies obtained from the Indonesian stock exchange from 2018 to 2022, The research method in this study is quantitative research. The sample selection technique used was purposive sampling and was obtained from 32 manufacturing companies so that the total number of obervation data was 160 data. The data analysis method in this study is multiple linear regression analysis using panel data regression analysis with a fixed effect model. The results of the study show that the capital structure variable has a positive effect on financial performance. The sales growth variable did not have a positive effect on financial performance. Liquidity and Environment, Social and Governance Rating have no effect on financial performance. The size of the company moderates the capital structure to financial performance. company size does not moderate sales growth to financial performance.